Citra Wanita dalam Novel Amira Cinta dari Tanah Surga Karya Suliwe - Surastina Surastina (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2016)
This study aims to identify and describe the image of women in the novels Amira Cinta Dari Tanah Surga by Suliwe which include: women images in getting love / attention, women images in getting loyalty. Women images in getting opinion right, and women images in getting the support of her husband in life. The method that used in this study was qualitative method with content analysis techniques. The focus of this research was the woman images in Amira Cinta Dari Tanah Surga novel by Suliwe. To achieve the objectives, the researcher used qualitative methods with content approach, that is, by analyzed the data in the form of sentences, paragraphs, or dialog that contains of women images. Since the data that analyzed was in the form of sentences and qualitative, the authors used qualitative data analysis, based on the content and structure of the existing sense. So, in analyzing the data and drawing the final conclusion, the authors did not use formulas statistical and hypothesis testing. Based on the research findings, it found 89 quotations in novel that contained of women images, that is: 1) 25 quotations of women images in getting love / attention, 2) 17 quotations of women images in getting loyalty, 3) 27 quotations of women images in getting opinion right, and 4) 20 quotations of women images in getting the support of her husband in life.Keywords: amira cinta dari tanah surga, citra wanita, novel.